Postpartum smoking relapse among women who quit during pregnancy: Cross‐sectional study in Japan. Issue 11 (22nd July 2013) - Yasuda, Takako; Ojima, Toshiyuki; Nakamura, Mieko; Nagai, Akiko; Tanaka, Taichiro; Kondo, Naoki; Suzuki, Kohta; Yamagata, Zentaro
Abstract Aim To determine the postpartum smoking relapse rate among women in Japan who quit smoking during pregnancy and to clarify factors related to smoking relapse. Methods A self‐administered questionnaire survey was conducted as a cross‐sectional study of all mothers of children who underwent health checkups after birth in randomly selected municipalities in Japan from May to July 2009. Using valid data of 20 601 mothers, smoking rate was calculated. In addition, χ2‐test and multiple logistic regression analysis were used to clarify related factors to the smoking relapse. Results The smoking rates among women were 15.8% at the time when they became pregnant, 5.1% during pregnancy and 11.3% after giving birth. Among women who smoked at the time they became pregnant, the smoking rate during pregnancy was 31.1%. Among women who quit smoking during pregnancy, the postpartum smoking relapse rate was 41.0%. The odds ratios (95% confidence interval) for factors in smoking relapse were 0.72 (0.60–0.88) for women spending time with their child in a relaxed mood, 0.67 (0.47–0.94) for women having someone to talk to on the Internet about childrearing, 1.94 (1.60–2.35) for women who worked and 3.37 (2.61–4.35) for women whose partner smoked after they gave birth. Conclusion It is hoped that future research will establish methods to further support smoking cessation and the continuation of smoking cessation after childbirth, and develop mechanisms to spread knowledge about the harm of smoking in society and encourage women not to start.